Calculation of the molecular properties of five cephalosporins: cephradine, cephalexin, cefadroxil, cefprozil and ceftobiprole - Elso Manuel Cruz Cruz; Eslhey María Sánchez Domínguez (Medisur, 2010)
Background: The side chains attached to the 7-amino cephalosporanic acid, the structural basis of cephalosporin, condition its molecular properties and cause differences in its pharmacological action. Molecular modeling contributes to further knowledge about this relationship. Objective: To calculate structural and electronic properties of five cephalosporins: cephradine, cephalexin, cefadroxil, cefprozil and ceftobiprole. Methods: A theoretical study using quantum mechanics methods to model the structure and electronic properties of the cephalosporins listed above was conducted. Molecular geometries were optimized with semi-empirical calculations, according to the parameterized number three model. The molecular properties were calculated following the density functional theory. The densities of atomic charges and the frontier orbitals were analyzed. Comparisons were established to measure the effect of substituents on the properties of the beta-lactam ring. All calculations were run on personal computers belonging to the Medical Sciences University of Las Tunas, from November 2009 to March 2010. Results: The structural parameters of the beta-lactam ring do not change as a result of changes in the side chains. The ring has a marked tendency to planarity. The ceftobiprole is different from the rest of the cephalosporins in the spatial disposition of the side chain, which facilitates access to the carbonyl carbon. There are no significant variations in the charge densities, especially in the positive charge of this carbon. Conclusions: The structure and electronic properties of the beta-lactam ring have no significant changes among modeled cephalosporins. The three dimensional structure of ceftobiprole favors a higher reactivity.